Pelatihan Tilawatil Quran Untuk Memperbaiki dan Memperindah Bacaan al-Quran Komunitas Muslimat NU Desa Jatiroto Kayen Pati - Luthfi, M. (LPPPM STAI Darul Hikmah Bangkalan, 2023)
The purpose of this service is to improve and beautify the Quran reading of the NU Muslim community in the Jatiroto village, Kayen, Pati. Tilawatil Quran is an activity to improve the reading of the Quran in accordance with applicable rules including recitation, sound, song, breath and fashahah. The NU Muslimat Community of Jatiroto Kayen Pati Village in organizing an event always includes Quran recitations in the agenda. Solid and militant cadres are potential for the NU Muslimat of Jatiroto Village. Behind this potential, the NU Muslimat of Jatiroto Village still lacks cadres who can recite Quran recitations, so the staff who carries Quran recitations are very limited. This training is one solution to recruite the stock of NU Muslimat cadres in Jatiroto Village so that they can bring Quran recitations in an event that is being held. The target of this training is NU Muslimat cadres in Jatiroto Village who are interested in participating in the training. The implementation of community service in the form of training uses an Asset based community development (ABCD) approach with six procedures including setting scenarios, revealing the past, dreaming of the future, mapping assets, planning actions as well as evaluation and learning. As a result of this dedication, participants in the Tilawatil Quran training had mastered basic Tajweed knowledge, were able to practice basic vocal, tone and breathing techniques.